Modern European thought : continuity and change in ideas, 1600-1950 - Baumer, Franklin L. (Franklin Le Van), 1913-1990. (New York : Macmillan, 1977)
This book is for anyone interested in ideas and their history. Despite its comprehensiveness, it is not primarily a survey or synthesis but rather an interpretation of modern intellectual history. Its specific purpose is to trace the development of one intriguing theme- perhaps the major theme- in modern man's way fo thinking about himself and his universe. That these is the sense of becoming rather than being.
Prologue -- The seventeenth century -- The eighteenth century -- The nineteenth century -- The twentieth century -- Epilogue.
Includes indexes.
Includes bibliographical references (p. 520-523).
ISBN 0-02-306450-1 Pbk : £5.95.
Keywords: Philosophy, Modern -- History; Europe -- Intellectual life